Description of the immature stages of Pentacomia (Mesochila) smaragdula Dejean 1825) (Coleoptera: Carabidae, Cicindelinae), with notes on the species distribution - Roza, André Silva; Mermudes, José Ricardo M. (Zootaxa, 2015)
The Atlantic Rainforest is one of the most threatened biomes of the world, with only 11−12 % of its original cover. The Cicindelinae are present in this biome with a relatively high diversity, but data of their immature forms are few. On the basis of six larvae and four pupae of Pentacomia (Mesochila) smaragdula we describe and illustrate the third larval instar of the larva and the pupa of this species. Notes on the species distribution are also given.